Analysis of the Effect of Leadership Behavior and Resource Competencyhumans to Organizational Performance With the Utilization of Information Technology as Intervening Variables at Prof Dr.Rdkandou Manado Hospital - Arlitha; Tawas, Hendra N.; Sumarauw, Jacky (European Journal of Life Safety and Stability (2660-9630), 2021)
A good Organizational Performance is an important factor for a company or the government institution. Companies will always strive so that every activity carried out achieves maximum results by doing it effectively in order to improve the Organizational Performance. The Organization Performance can be used as a measure of the success of an organization within a certain period of time as an input for the organizational performance. The aims of this research is to determine the Influence of Leadership Behavior and HR Competence on Technology Utilization and The Influence of Leadership Behavior, HR Competence and Utilization of Information Technology on Organizational Performance. The population in this study involved civil servants at the Hospital Prof. Dr.RDKandou Manado which amounted to 1,233 respondents and used a random slovin-proportional method and obtained 95 respondents. The research techniques using path analysis. The results of hypothesis testing show that 1) Leadership Behavior has a positive and significant effect on the Utilization of Information Technology, 2) HR Competencies have a positive and significant effect on the Utilization of Information Technology 3) Leadership Behavior has a positive and significant effect on organizational performance 4) HR Competencies have a positive and significant impact on Organizational performance and 5) Utilization of Information Technology has a positive and significant effect on organizational performance. HR Competence, Utilization of Information Technology and Organizational Performance.